Vivian Maier und der gespiegelte Blick: Fotografische Positionen zu Frauenbildern im Selbstporträt - Köffler, Nadja (transcript, 2019)
After the sensational discovery of Vivian Maier's photographic oeuvre, the work of Vivian Maier is now presented: for the first time, a well-founded iconographic analysis of her work is presented, which also traces Maier's feminism and her self-image as an artist.